Freddy the Frogcaster and the huge hurricane - Dean, Janice, 1970- (Freddy the Frogcaster, 2015)
"Freddy the Frogcaster is tracking the weather at Frog News Network when he realizes a huge hurricane is coming! Can the town of Lilypad prepare for the storm in time? Can Freddy report the weather on TV and make sure his family and friends are safe?"--